Viabilidade do uso de alfa-amilase de malte de cevada na hidrólise do amido da batata-doce como alternativa na fabricação de aguardente - Silva, Manuelly Stopiello Yanaguisawa da (2025)
Aguardente is a distilled beverage widely consumed in Brazil and around the world. Sweet potato (Ipomoea batatas) is a nutrient-rich and starchy vegetable with great potential in the food industry. It stands out for its wide variety of cultivars, easy maintenance, good tolerance to periods of water stress, and low production cost. This work aimed to evaluate the feasibility of using barley malt alpha-amylase enzyme for the hydrolysis of sweet potato starch as an alternative in the production of aguardente. After the enzyme extraction and starch hydrolysis verification, the best conditions were analyzed and data were collected to perform the experimental planning developed using Statistica software. The best condition for must production was a 1:2 ratio between sweet potato and water, with an enzyme action time of 35 minutes, as proven by experiment 13. Alcoholic fermentation occurred using Saccharomyces cerevisiae, followed by the distillation and bottling process. Subsequently, physicochemical analyses (alcohol content, pH, and °Brix) of aguardente were carried out, as well as the evaluation of antioxidant potential (DPPH and ABTS) and analyses of bioactive compounds (total phenolic compounds and total anthocyanins). Through the iodine test, it was possible to prove the efficiency of barley malt extraction, making the must more accessible for fermentative processes and enabling the development of aguardente. The physicochemical analyses of aguardente were within the expected standards, with an alcohol content of 37% (v/v) and pH 4.42. The antioxidant activity and phenolic compounds showed variations compared to studies by other authors, considering the source of the raw material used and the processes involved in its production.